Slum plays, salvation stories, and crook pictures: the gangster regeneration cycle and the prehistory of the gangster genre - Heffernan, Nick (Indiana University Press, 2017)
Recent scholarship exhorts film historians to attend to production cycles in order to interrogate established conceptions of genres. This essay identifies and examines a neglected cycle of gangster regeneration films that flourished between 1910 and 1925 and constituted the prehistory of a genre usually identified with the early 1930s. The gangster regeneration cycle drew from the “slum plays” and “salvation stories” of stage melodrama a set of narrative formulas and thematic concerns that reflected the influence of Progressive ideology. In its attitude to social reform and gender, it stands in sharp distinction to the canonical gangster cycles that succeeded it.